1993
DOI: 10.1287/mnsc.39.9.1163
|View full text |Cite
|
Sign up to set email alerts
|

On the Extensive Number of Plays to Achieve Superior Performance with the Geometric Mean Strategy

Abstract: The advantages of the Geometric Mean or Log Strategy have been well documented and recommended by many because a follower of this strategy will ultimately outperform in the long-run any other significantly different strategy, almost surely. This paper provides both theory and evidence to indicate that the "long-run" can be quite long in risky situations. These cases are typified by many business ventures and undiversified speculative investments in OTC securities. On the other hand, it is shown that the Log St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…To overcome this puzzle, J. Kelly, [12] initiated an approach that led to a vast literature [10,[13][14][15][16][17][18][19][20][21] that tested, extended and applied practically his proposal. The mathematical setting that Kelly considered was the following.…”
Section: The Kelly Terminologymentioning
confidence: 99%
“…To overcome this puzzle, J. Kelly, [12] initiated an approach that led to a vast literature [10,[13][14][15][16][17][18][19][20][21] that tested, extended and applied practically his proposal. The mathematical setting that Kelly considered was the following.…”
Section: The Kelly Terminologymentioning
confidence: 99%
“…Previous studies on Kelly-betting (expected log utility maximization) have revealed that this decision rule promotes wagers that are too risky for many peoples' tastes (Li 1993, Aucamp 1993, MacLean et al 2004. The issue then is whether the log score is relevant to decision makers who do not have log utility.…”
Section: Resultsmentioning
confidence: 99%
“…Although the rationality of investors practising Kelly strategies is discussed in the literature Samuelson (1963), Aucamp (1993), Benartzi and Thaler (1999), more recent works like Ross (1999), Christensen (2005) affirm that under certain conditions on the utility function, it can also be rational to use geometric strategies and that 'expected utility theory is rich enough to encompass acceptance as well as rejection of sequences of good bets Ross (1999, p. 325)'.…”
Section: A General Trading Modelmentioning
confidence: 99%